Revitalisasi Daun Kelor: Implementasi Pelatihan Pengolahan Daun Kelor Untuk Pengurangan Prevalensi Stunting - Suprojo, Baskara; Lerieana Rachma Trianti (Penerbit Goodwood, 2025)
Purpose: Kelor Village, as the name suggests, is famous for its high productivity of raw materials, namely moringa leaves. Moringa leaves are one of the food ingredients that can reduce malnutrition for pregnant women and malnutrition for infants. However, the reality is the opposite, data on the nutritional status of toddlers in November 2022 shows that Kelor Village has a stunting percentage of 38.5%. The purpose of this training is to socialize the urgency of stunting and train the community in processing moringa leaves. Methodology/approach: This research uses a descriptive qualitative approach to determine the extent to which the Kelor Village community, especially posyandu cadres, utilize their potential in dealing with health, economic and other problems. Results/findings: The results of this training showed a change in perspective about moringa leaves and the community was moved to process moringa leaves to be used as Supplementary Food Provision (PMT) to reduce stunting rates in Kelor Village. After this training, it is hoped that the community will be motivated to utilize and process moringa leaves more widely so that it can become a job opportunity for the local community. Limitations: Moringa leaf processing training for stunting prevention and community income improvement in Kelor Village. Contribution: The Moringa leaf food processing socialization and training program is an initiative by the Yogyakarta government affiliated with IDI for Kelor Village. This training is provided to the residents of Kelor Village to explore the processing of Moringa leaves, with the aim of developing it into a business opportunity for Moringa leaf food products.